The Effectiveness of Behaviour Based Safety (BBS) in Accident Prevention at a Pine Timber Processing Plant in Nyanga District, Zimbabwe - Jerie, Steven; Jenya, Baldwin (LAR Centre Press, 2022)
The aim of this study was to assess the effectiveness of Behaviour Based Modelling (BBM) in the timber processing operationsat a pine timber processing plant in Nyanga district in Eastern Zimbabwe. A detailed descriptive study was undertaken on the effectiveness of BBM in the timber processing operations. A sample size of 20% of all the 600 employees directly involved in timber processing operations was used in data collection. Direct field observations, interviews and questionnaires surveys were used as primary sources of data collection. Secondary data was acquired from the division`s local clinic and the Safety, Health and Environment (SHE) department at the timber processing plant. Data collected was analysed using the statistical and descriptive methods. The study showed that BBM is accomplishing its intended goals although management support could increase with the prime focus centered on timber processing operations. Behaviour Based Modelling has changed employee attitudes in dealing with occupational related accidents and environmental pollution through the “brother`s keeper” attitude. Before the implementation of Behaviour Based Management, the pine processing plant recorded high numbers (triple figured digits) of near misses and occupational related accidents. However, the introduction of Behaviour Based Modelling resulted in the recording of double figured digits in occupational related accidents and zero major environmental spillages by the end of 2016. Improvements on the existing operational procedures of Behaviour Based Modelling could, however, improve its effectiveness. The Safety, Health and Environment department should ensure that employees have the right to refuse to work under unsafe and unhealthy work conditions.